Higher serum interleukin-17A levels as a potential biomarker for predicting early disease progression in patients with hepatitis B virus-associated advanced hepatocellular carcinoma treated with sorafenib. (July 2017) - Cho, Hyo Jung; Kim, Soon Sun; Nam, Ji Sun; Oh, Min Jung; Kang, Dae Ryong; Kim, Jai Keun; Lee, Jei Hee; Kim, Bohyun; Yang, Min Jae; Hwang, Jae Chul; Lim, Sun Gyo; Shin, Sung Jae; et al.
Highlights: Higher IL-17A is a potential biomarker of poor PFS in sorafenib treated HCC patients. Further basic research about the role of IL-17A in HCC progression would be required. Serum FGF-2 level is a prognostic biomarker of OS in sorafenib treated HCC patients. Serum FGF-2 shows positive correlation with parameters representing hepatic reservoir. Abstract: Background: Although sorafenib is the only available drug with proven efficacy for patients with advanced hepatocellular carcinoma (HCC), the clinical efficacy of sorafenib is variable and unpredictable. The aim of the current study was to identify potential serum biomarkers predicting cancer progression and overall survival (OS) in patients with hepatitis B virus (HBV)-related advanced HCC treated with sorafenib. Methods: Thirty-four patients with HBV-related advanced HCC (modified Union for International Cancer Control [UICC] stage IVa or IVb) treated with sorafenib for more than 4 weeks were retrospectively enrolled. Using a Luminex 200 system, 11 cytokines including interleukin-17A (IL-17A) were measured in baseline serum samples prior to sorafenib administration. Several clinical factors and the serum concentrations of the 11 cytokines were analyzed using Cox regression analysis. Results: In the analysis of progression-free survival (PFS), older age (year; hazard ratio [HR] = 1.07; 95% confidence interval [CI] = 1.00–1.15; P  = 0.046) and higher baseline serum IL-17A level (>1.94 pg/mL; HR = 19.96; 95% CI = 3.32–119.86; P  = 0.001) were identified as significant risk factors for early progression with good predictive power (Harrell's C = 0.817, standard error estimates (se) = 0.085). In the analysis of OS, higher Child-Pugh score (>5; HR = 2.35, 95% CI = 1.09–5.10, P  = 0.030) and lower serum baseline fibroblast growth factor-2 level (≤20.57 pg/mL; HR = 3.24, 95% CI = 1.22–8.60, P  = 0.018) were identified as negative predictive factors for OS, even though the model did not have significant predictive power (Harrell's C = 0.634, se = 0.062). Conclusion: A higher serum IL-17A level is a potential biomarker for predicting poor PFS in patients with HBV-related advanced HCC treated with sorafenib.